Optimization of ex vivo permeability characteristics of berberine in presence of quercetin using 32 full factorial design - Sarika Narade, Yogesh Pore (Journal of Applied Pharmaceutical Science, 2019)
The aim of the present work was to investigate permeability characteristics of an anticancer berberine chloride, in presence and absence of bioenhancer quercetin on goat intestine using Franz diffusion cell. A 32 full factorial design approach was employed to investigate the effect of independent variables such as the concentration of bioenhancer (X1) and pretreatment time (X2) on dependent variable % cumulative drug release (% CDR) (Y) using design expert software. The effect of quercetin was examined at three different levels of pretreatment time (30, 45, and 60 minutes) and at three different concentrations (2, 6, and 10 mg) on goat intestine. The apparent permeability (Papp), flux (J), and enhancement ratio (ER) were determined. Further, in vitro anticancer activity of optimized batch was performed on various cancer cell lines K562, A459, and Hela. During pretreatment studies, it was observed that an increase in the concentration of quercetin yielded a positive effect on % CDR while the increase in pretreatment time by quercetin had a detrimental effect on % CDR. When goat intestine was pre-treated for 30 minutes with 10 mg of quercetin, 90.91% ± 1.66% CDR was obtained while the minimum value of 17.45% ± 2.12% CDR was observed at 2 mg quercetin pre-treated for 60 minutes. In vitro anticancer activity of optimized batch demonstrated non-significant effect as compared with parent drug. In conclusion, quercetin could be successfully utilized as bioenhancer to improve ex vivo permeability of berberine chloride, which would be expected to improve its bioavailability and reduce the dose resulting in improved patient compliance.
Keywords: Berberine chloride, bioenhancer quercetin, full factorial design, ex vivo permeability study, in vitro anticancer activity.